Grouping Factors and the Reverse Contrast Illusion. (December 2015) - Economou, Elias; Zdravković, Sunčica; Gilchrist, Alan
In simultaneous lightness contrast, two identical gray target squares lying on backgrounds of different intensities appear different in lightness. Traditionally, this illusion was explained by lateral inhibitory mechanisms operating retinotopically. More recently, spatial filtering models have been preferred. We report tests of an anchoring theory account in which the illusion is attributed to grouping rules used by the visual system to compute lightness. We parametrically varied the belongingness of two gray target bars to their respective backgrounds so that they either appeared to group with a set of bars flanking them, or they appeared to group with their respective backgrounds. In all variations, the retinal adjacency of the gray squares and their backgrounds was essentially unchanged. We report data from seven experiments showing that manipulation of the grouping rules governs the size and direction of the simultaneous lightness contrast illusion. These results support the idea that simultaneous lightness contrast is the product of anchoring within perceptual groups.